2001
DOI: 10.1128/aem.67.6.2754-2759.2001
|View full text |Cite
|
Sign up to set email alerts
|

Purification, Characterization, and Functional Role of a Novel Extracellular Protease from Pleurotus ostreatus

Abstract: A new extracellular protease (PoSl; Pleurotus ostreatus subtilisin-like protease) from P. ostreatus culture broth has been purified and characterized. PoSl is a monomeric glycoprotein with a molecular mass of 75 kDa, a pI of 4.5, and an optimum pH in the alkaline range. The inhibitory profile indicates that PoSl is a serine protease. The N-terminal and three tryptic peptide sequences of PoSl have been determined. The homology of one internal peptide with conserved sequence around the Asp residue of the catalyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
1
17

Year Published

2002
2002
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(75 citation statements)
references
References 27 publications
2
55
1
17
Order By: Relevance
“…The collected and concentrated supernatant was used for L-aspargenase studies. L-aspargenase was purifiedand used for characterization studies according to the methods of Palmieri, et al [44].…”
Section: Precipitation With Ammonium Sulfatementioning
confidence: 99%
“…The collected and concentrated supernatant was used for L-aspargenase studies. L-aspargenase was purifiedand used for characterization studies according to the methods of Palmieri, et al [44].…”
Section: Precipitation With Ammonium Sulfatementioning
confidence: 99%
“…This observation indicates an inactivation over time of the laccase already present at the time point of cycloheximide addition. Proteolysis, which is often implicated in fungal laccase turnover (36,54), and the concomitant suppression of further laccase production by the cycloheximide might explain the observed decrease in laccase activities.…”
Section: Resultsmentioning
confidence: 99%
“…However, we have not purified Lac1 or Lac3 laccases because of their low concentrations. Recently it was shown that extracellular proteases may affect the concentrations of secreted laccases (33), which could explain why we were unable to obtain larger amounts of Lac1 and Lac3.…”
Section: Discussionmentioning
confidence: 99%